The art of balance: Engineering of structure defects and electrical conductivity of α-MnO2 for oxygen reduction reaction. (1st September 2018) - Lan, Bang; Zheng, Xiaoying; Cheng, Gao; Han, Jiaxi; Li, Wanping; Sun, Ming; Yu, Lin
Abstract: Manganese dioxides have emerged as promising candidates for catalyzing oxygen reduction reaction (ORR). To promote ORR activity, intensive effort has been made to engineer manganese dioxides with either abundant defects or high electrical conductivity. In this work, a balance in engineering between defects and electrical conductivity in controllable engineering of α-MnO2 is successfully demonstrated. By controlling the reaction temperature (60, 80, and 140 °C), three-dimensional (3D) dandelion-like α-MnO2 microspheres were synthesized with different degrees of defects and electrical conductivities. The α-MnO2 with either more defects or higher electrical conductivity should possess better ORR performance. However, with increasing synthesis temperature, the defects in the as-prepared samples decreased, while the electrical conductivity increased. Therefore, the preparation α-MnO2 at 60 °C or 140 °C for the best ORR performance remains unclear. As determined by electrochemical measurement, the α-MnO2 prepared at 80 °C with moderate defects and electrical conductivity exhibits superior ORR performance with a potential of 0.79 V at a current density of −3 mA cm −2, which is considered outstanding for manganese oxides. This work shed new light on the strategy to simultaneously regulate the defect and electrical conductivity, and a balance between them should produce an effective catalyst for ORR. Graphical abstract: Image 1 Highlights: Three α-MnO2 samples were fabricated under different temperature. α-MnO2 -80 exhibits the best ORR performance among three samples. A balance in defect and electrical conductivity leads to the optimized ORR activity.